"Carrot and stick" leadership style: Can it predict employees' job satisfaction in a contemporary business organisation?. Issue 3 (5th September 2016) - Dartey-Baah, Kwasi; Ampofo, Emmanuel
Abstract : Purpose: The purpose of this paper is to examine the relevance of "carrot and stick" (transactional) leadership style in predicting employees' job satisfaction in a modern business organization. Design/methodology/approach: The study was cross-sectional in nature and made use of structured questionnaire to collect data. Stratified and simple random sampling techniques were used to select the respondents. In total, 215 questionnaires were returned by respondents out of the 220 administered. Taylor and Bowers (1974) overall job satisfaction questionnaire and Bass and Avolio (2004) multifactor leadership questionnaire, were used to measure job satisfaction ( α =0.812) and transactional leadership style ( α =0.761), respectively. Simple linear regression was also used to predict the relationship between the constructs. Findings: Results indicated significant and positive relationship between managers transactional leadership style and employees overall job satisfaction ( β =0.292, p <0.001). Moreover, contingent reward ( β =0.313, p <0.001) and management by exception (active) ( β =0.208, p <0.001) were, respectively, found to be statistically significant and positively related with job satisfaction. However, there was no significant relationship between management by exception (passive) and job satisfaction. Originality/value: This study adds to research that transactional leadership is broadly ideal for employees of manufacturing firms in Ghana where tasks are routine, objectives are clearly stated and work outputs can easily be measured.